Structure and content of training of the qualified runners on middle distances in annual cycle of preparation - Tu Yanhao; Lydmyla Shesterova (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to develop and to confirm experimentally the efficiency of the program of one-cycle creation of the training process of the qualified runners on middle distances in annual cycle of preparation. Materials & Methods: 40 qualified runners on middle distances took part in the research, 20 of which mainly lived in mountain conditions and 20 - mainly on the plain. The following methods were used during the research: analysis and synthesis of references, analysis of documentary materials, pedagogical observation. Results: the structure of annual macrocycle of training of runners on middle distances with the use of trainings in mountain conditions is presented. Content of mesocycles of preparation, volumes and orientation of training loads at them are directed. Conclusions: the correct and rational connection of means of training of runners on middle distances in mountain conditions and on the plain influences positively the level of preparedness and promotes the professional development of sportsmen.